The Comparative Study of Accreditation Standards of Medical Sciences Educational Programs in Iran and Some Other Countries of the World - Parvaneh Sharifi; Alireza Manzari Tavakoli; Mitra Kamyabi; Zahra Zeinaddiny Meymand (Kerman University of Medical Sciences, 2021)
Background: Program accreditation is a quality assurance educational program implemented in many countries.Objectives: This study aimed to compare program accreditation standards of the Ministry of Health of Iran with several selected countries and to extract program accreditation standards to benefit from the experiences of other countries.Methods: The present descriptive-comparative study was performed in 2020. The information required for the study was collected by searching on the Internet on valid websites of accreditation institutes of medical sciences and higher education in Iran and other countries. Among them, the World Federation for Medical Education (WFME) program accreditation standards and eight countries from different continents were compared with Iran. The research was conducted using the Beredy model.Results: The results showed that the standards in the studied programs were significantly different both quantitatively and qualitatively. It was also found that the accreditation standards of educational programs in Iran, Kazakhstan, and the WFME were consistent regarding the areas' number and titles, but there was a difference in the number and titles of the criteria and indicators.Conclusion: Considering the vital role of graduates of medical sciences in promoting community health and also given the current and particular situation and the global conflict with COVID-19 epidemic, which has disrupted face-to-face education and evaluation at all educational levels, upgrading and improving the quality of medical education programs seems necessary more than ever. Therefore, to evaluate and promote the quality of these programs, it is suggested to codify accreditation standards of educational programs locally and according to the current conditions.